Desenvolvimento de iogurte tipo grego caprino, adicionado de extrato aquoso de inhame e caseína em pó de leite caprino - Santos, Ramon Araújo dos (2020)
In order to add value to the goat Greek-style yogurt, it was used in its aqueous yam extract (Dioscorea cayennensis) and goat milk casein powder. Yam is rich in fiber and antioxidant compounds that help treat various diseases such as diabetes and cancer and as goat milk proteins are precursors of bioactive peptides that perform antioxidant, antihypertensive and antigenic action. Therefore, yogurts were altered, being variables of the study as aqueous yam extract and goat milk casein powder, since yam is an excellent source of starch, and starches and milk proteins that have some hydrocolloid component. Thus, this study aimed to analyze the influence of the addition of aqueous yam extract and goat milk casein powder on the physicochemical, technological, microbiological and sensory characteristics of the goat Greek-style yogurt. Four formulations were elaborated: The IC (control yogurt) composed only of goat milk. IP composed of goat milk and 2% goat milk casein powder. IPI1 composed of 90% goat milk, 10% aqueous yam extract and 2% goat milk casein powder. IPI2 composed of 80% goat milk, 20% aqueous yam extract and 2% goat milk casein powder. In the first study has been analyzed as the physicochemical and technological characteristics of the goat Greek-style yogurt. IPI1 presents more positive results, obtaining higher viscosity, higher water holding capacity and higher protein content, while IPI2 presented the best results for the number of grains per gram and susceptibility to syneresis, but lower protein content, fat and viscosity. The IP presented the highest yield, however, it was more susceptibility to syneresis, and the IC the highest fat content and results not favorable to water holding capacity number of grains per gram and yield. The second study analyzed the microbiological and sensory characteristics of goat Greek-style yogurt. All samples meet the microbiological requirements set by national legislation for fermented milks. The IP presents more positive results in sensory analysis, obtaining as the largest media the resources of texture, color, odor, taste and overall evaluation, with acceptance index of 84.22%, higher average for purchase intention and greater preference. The IC had an acceptance index of 82.00% and the IPI1 of 70.33%. The IPI2 had the lowest media for all attributes, with an acceptance index of 66.44%, however, to be considered accepted, and should reach at least 70%, on the other hand, with the addition of 20% aqueous yam extract and 2% goat milk casein powder make this yogurt a potentially functional product. The results obtained in the studies, an addition of aqueous yam extract show better results in physicochemical and technological characteristics, while goat milk casein powder provides better results in physicochemical, technological and sensory characteristics, contributing to the development of a new dairy product with enhanced features compared to IC and nutritional quality, allowing it to expand as goat dairy product options found in the market.